2020
DOI: 10.1103/physrevfluids.5.084304
|View full text |Cite
|
Sign up to set email alerts
|

Particle accumulation structures in noncylindrical liquid bridges under microgravity conditions

Abstract: The emergence of Particle Accumulation Structures (PAS) in non-cylindrical liquid bridges (LB) is studied numerically for a high Prandtl number liquid considering microgravity conditions. Simulations are conducted in the framework of a finite-volume (Eulerian) approach with non-isodense particles being tracked using a Lagrangian, one-way coupling scheme. First, the threshold of the Marangoni-flow instability is determined as a function of the aspect ratio and the volume of liquid held between the supporting di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…All the simulations reported in the present work have been carried out by means of the transient incompressible "buoy-antBoussinesqPimpleFoam" solver available in the Open-FOAM package, while the thermocapillary stress condition was implemented anew and thoroughly tested by our group (see e.g., Capobianchi and Lappa (2020)). Moreover, the boundary/interface-particle interaction schemes available in the native OpenFOAM releases have been modified to take into account the actual dimension of the particles (see further below for a more detailed discussion of this model).…”
Section: Numerical Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…All the simulations reported in the present work have been carried out by means of the transient incompressible "buoy-antBoussinesqPimpleFoam" solver available in the Open-FOAM package, while the thermocapillary stress condition was implemented anew and thoroughly tested by our group (see e.g., Capobianchi and Lappa (2020)). Moreover, the boundary/interface-particle interaction schemes available in the native OpenFOAM releases have been modified to take into account the actual dimension of the particles (see further below for a more detailed discussion of this model).…”
Section: Numerical Methodologymentioning
confidence: 99%
“…Closure of the mathematical problem also requires the introduction of the tangential stress boundary condition needed to account for the thermocapillary force arising as a consequence of thermally induced surface tension imbalance. Assuming an inviscid surrounding gaseous phase this condition simply reads (see, e.g., (Capobianchi and Lappa 2020)) where is the dynamic viscosity, is the unit normal vector at the liquid-gas interface, and the operator s represents the surface gradient, i.e., the projection of the vector gradient on the interface of the liquid bridge.…”
Section: Flow Dynamicsmentioning
confidence: 99%
“…The dimensionless numbers appearing in the above set of equations are the Grashof number, Gr = gβΔTL 3 /ν 2 , the Prandtl number, Pr = ν/α, and the Reynolds number, Re = σ T ΔTL/ρ 0 ν 2 , where α and β are the thermal diffusivity and thermal expansion coefficient of the fluid, respectively, ν is its kinematic viscosity and σ T = −∂σ/∂T| T=T 0 . For consistency with a companion work (Capobianchi & Lappa 2020), in the following we shall refer to the Marangoni number, Ma = RePr, rather than Re.…”
Section: Mathematical Descriptionmentioning
confidence: 99%
“…As illustrated, e.g. by Capobianchi & Lappa (2020), experiments dealing with a variety of fluids and particle types (see the literature cited in the introduction) have shown that once particles are inside the attractor (the KAM torus), even if φ increases locally to a significant extent, inter-particle forces or other 'back influence' effects are not intense enough to force particles to leave the attractor. This may be regarded as the sought justification about the effective possibility to neglect two-and four-way effects even when all the particles are concentrated in a thin region (the PAS itself).…”
Section: Particle Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation